Views on COVID-19 vaccination among residents of Eldoret, Kenya during the 2021 vaccine rollout - Edna N. Bosire; Allie Cho; Lucy Wambui Kamau; Violet Bosire; Emily Mendenhall (Taylor & Francis Group, 2023)
ABSTRACTThe Government of Kenya initiated COVID-19 vaccination program in March 2021. However, vaccine uptake remains low, especially in rural areas in Kenya. We interviewed 40 residents of Eldoret town to explore the knowledge, beliefs, and meanings they attach towards vaccines generally, and why they chose to vaccinate or not. Two-thirds of our participants perceived themselves to be at risk of COVID-19 infections. About half demonstrated willingness to be vaccinated and about a third had been vaccinated. All participants were knowledgeable about the broader benefits of vaccination. Yet, widespread beliefs that vaccination programmes target children and pregnant women decreased vaccine acceptance. Also, we found that concerns about vaccine safety, lack of knowledge, misinformation from social media, and conspiracy theories contributed to COVID-19 vaccine hesitancy in Eldoret. Low COVID-19 vaccination rates and hesitancy - even when the vaccines are accessible and free in Kenya - cannot be ignored. The current COVID-19 vaccination prioritisation schedule (distinct from the usual structure where children, childbearing women are prioritised) and beliefs that older people are targeted to test vaccines efficacy must be addressed through improved communication and mass education. More research is needed to investigate the socio-economic, political, and historical factors that influence vaccine hesitancy in Kenya.